2018
DOI: 10.2196/10668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Internet-Based Interventions on Caregiver Mental Health: Systematic Review and Meta-Analysis

Abstract: BackgroundThe health of informal caregivers of adults with chronic conditions is increasingly vital since caregivers comprise a large proportion of supportive care to family members living in the community. Due to efficiency and reach, internet-based interventions for informal caregivers have the potential to mitigate the negative mental health outcomes associated with caregiving.ObjectiveThe objective of this systematic review and meta-analysis was to examine the impact of internet-based interventions on care… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 46 publications
8
125
0
2
Order By: Relevance
“…Consistent with our findings, prior evidence has been found for the benefit of internet-based intervention programs on mental health, particularly for depression, stress and distress, and anxiety. The types of interventions that predominated as efficacious included information and education with or without professional psychological support, and, to a lesser extent, combined with peer and psychological support (Sherifali et al, 2018). Nevertheless, in an internetbased intervention comprising five structured confrontational writing assignments, for individuals who experienced the death of a first-degree relative and who were significantly distressed, although writing decreased feelings of emotional loneliness and increased positive mood, writing did not affect grief or depressive symptoms.…”
mentioning
confidence: 99%
“…Consistent with our findings, prior evidence has been found for the benefit of internet-based intervention programs on mental health, particularly for depression, stress and distress, and anxiety. The types of interventions that predominated as efficacious included information and education with or without professional psychological support, and, to a lesser extent, combined with peer and psychological support (Sherifali et al, 2018). Nevertheless, in an internetbased intervention comprising five structured confrontational writing assignments, for individuals who experienced the death of a first-degree relative and who were significantly distressed, although writing decreased feelings of emotional loneliness and increased positive mood, writing did not affect grief or depressive symptoms.…”
mentioning
confidence: 99%
“…The negative effects of caring for someone with dementia have been well reported, as well as the challenges which caregivers face including elevated levels of depressive symptoms, poorer physical health and decreased quality of life [36][37][38]. Several systematic reviews including the one published as part of the current study have demonstrated the benefits of internet-based interventions for caregivers living with adults with chronic conditions, including dementia [39]. However, there are few intervention studies which have focussed on supporting caregivers towards the end of life.…”
Section: Discussionmentioning
confidence: 79%
“…Despite the increase in research in this area -it has been estimated that the number of publications in this eld increases by 13% each year, including several systematic reviews -we could nd very little published with respect to the implementation of web-based caregiver interventions. (9)(10)(11)(23)(24)(25)(26) Moreover, many of the interventions described in the literature do not appear to be more broadly accessible outside of their research context. To our knowledge, no previous research has used the CFIR framework to study webbased caregiver interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based caregiver interventions may be quite heterogeneous, and may include different components such as health information, education, peer support, professional support, online monitoring, or combinations of these components. (11) Rarely do educational interventions in the literature describe their instructional design or report whether or not they conformed with best practices in multimedia learning.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation